PENERAPAN METODE DISKUSI SYNDICATE GROUP UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS V SDN BERU 02 WLINGI - Amin, Saiful; Khotimah, Siti (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2016)
This study aims to apply the syndicate group discussion method to increase students' learning activeness of fifth class in SDN (public elemantary school) Beru 02 Wlingi on legislation central and local levels matter. This type of research is a classroom action research. Collecting data using observation sheet and field notes. Data were analyzed using descriptive analysis. The results of study showed that the syndicate group discussion method can increase students' learning activeness, with increase the average score from the first cycle to the second cycle is 23.67. The suggestion that need to regulate the allocation of time on discussion and better manage classes with the implementation of learning.Keywords: syndicate group discussion method; students' learning activenessThis study aims to apply the syndicate group discussion method to increase students'learning activeness of fifth class in SDN (public elemantary school) Beru 02 Wlingi onlegislation central and local levels matter. This type of research is a classroom actionresearch. Collecting data using observation sheet and field notes. Data were analyzedusing descriptive analysis. The results of study showed that the syndicate groupdiscussion method can increase students' learning activeness, with increase the averagescore from the first cycle to the second cycle is 23.67. The suggestion that need toregulate the allocation of time on discussion and better manage classes with theimplementation of learning.Keywords: syndicate group discussion method, students' learning activeness